FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN KERJA DOKTER SPESIALIS TERHADAP PELAKSANAAN BPJS KESEHATAN DI RUMAH SAKIT PANTI WILASA DR. CIPTO - Shabrina Hasnaulia Safarah; Bagoes Widjanarko; Zahroh Shaluhiyah (Jurnal Kesehatan Masyarakat (Undip), 2018)
National health insurance (BPJS Kesehatan) is an Indonesian governmenting program that aims to improve the Indonesians health. In the program’s implementation, specialist hold an important role for the hospital. Therefore the specialist satisfaction is very influential to the hospital performance. The purpose of this study is to describe characteristics and its relation in specialist job satisfaction on the implementation of national health insurance.This research is quantitative study with cross sectional design. The total populations are 56 specialist working in dr. Cipto Panti Wilasa Hospital Semarang. Interview with quesionnaire was used to collect the data. Univariat and bivariat analysis was used in this research. Most specialist has an age range from 33-47 years old (57,5%), the majority of specialist’s gender is male (70%), most specialist have specialist as their last education (80%), with working period mostly for 4 years (55%), the majority of specialist is partner specialist (82,5%), most of specialist work in 3 workplace (57,5%), most specialist doesn’t have structural position (95%), and the majority of specialist’s income is Rp 10.000.000 – Rp 50.000.000,-. Chi square test result show that age is related to medical income as subvariabel of satisfaction, (p=0,012), and total work place related to supervision as subvariabel of satisfaction (p=0,011). There is no relation among job satisfaction and age (p=0,433), gender (p=0,297), level of education (p=1,000), working period (0,638), working status (p=1,000), total working place (p=0,154), structural position (p=1,000), and income (p=0,482).It is advisable to review clinical pathway need based on hospital’s data, local condition, and daily census towards high incident rate and costly cases, conduct monitoring and evaluation towards clinical pathway implementation in hospital, further review on INA CBG’s rates along with IDI, cooordination meeting with specialist as health provider in National Health Insurance.